Pharmacological Activities of Senna obtusifolia Linn.: A Medicinal Plant of Bangladesh - Anisuzzaman, Md; Ahsan, Md Qamrul; Kuddus, Md Ruhul; Rashid, Mohammad Abdur (Bangladesh Pharmaceutical Journal, 2015)
The crude methanol extract of seed of Senna obtusifolia Linn. has been investigated for anxiolytic, antiatherothrombosis, membrane stabilizing and alpha-amylase inhibitory activities. The anxiolytic activity was examined in mice by using the hole cross and open field test (OFT). The anti-atherothrombosis activity was evaluated and compared with that of standard streptokinase. The membrane stabilizing activity was tested by using hypotonic solution- and heat-induced hemolysis of human erythrocyte. The plant extract was also assessed for anti-diabetic activity through in vitro ?-amylase inhibitory potential. The ?-amylase inhibitory activity of S. obtusifolia was measured using the starch-iodine method. The crude extract of S. obtusifolia showed moderate anxiolytic activity. In the in-vitro anti-atherothrombosis test, the extract exhibited mild activity as compared to the standard, streptokinase (81.53%). In membrane stabilizing activity test, the plant extract at 1.0 mg/ml inhibited the heat-induced hemolysis of RBCs by 56.37% whereas the standard acetyl salicylic acid (ASA) demonstrated 71.36% inhibition of hemolysis. Our results revealed that the extract produced dose-dependent prevention of digestion of carbohydrates by inhibiting ?-amylase. These findings demonstrated that S. obtusifolia may be a good candidate for further analysis because of its effective pharmacological properties. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22338 Bangladesh Pharmaceutical Journal 17(2): 182-186, 2014